Discourse studies in public communication - Crespo Fernández, Eliecer (Discourse approaches to politics, society, and culture ;, 2021)
"The collection of articles in Discourse Studies in Public Communication illustrate that public communication is a fascinating, evidence-based storehouse for research in discourse analysis. The contributions to this volume - in the spheres of political rhetoric, gender and sexuality, and corporate and academic communication - provide good evidence of contemporary social structure, social phenomena, and social issues. In this way, following the parameters of different analytical frameworks (critical discourse analysis, cognitive metaphor theory, appraisal theory, multimodality, etc.), the contributors address not only the linguistic aspects of texts but also, and more importantly, the cultural and cognitive dimensions of public communication in a range of real life communicative contexts and kinds of discourse. Although the volume is addressed, first and foremost, to readers with diverse interests in English linguistics, it may also prove valuable to scholars in other non-linguistic research fields like communication studies, social theory, political science, or psychology"--